The Advocacy Coalition Framework: A Study On Malaysian National Water Resources Policy - Ismail, Junaida (2020)
Public policy is an alternative course of action taken by the government to address problem or matter of the public that is important to the nation. Charles L. Cochran and Eloise F. Malone (2005) defined public policy as political decisions of the implementation of programs to achieve societal goals. There are four sequences of phase that are involved in a public policy process. The most important stage is formulation where it involves the formulation of the course of actions and recommendations for selected policy agenda. The problem statement of this study is to understand the development of coalition among the actors, during the process of the National Water Resources Policy (NWRP) formulation. The research objectives are (i) to determine the pattern of previous eperiences in relation to coalition among actors; (ii) to identify the frequencies of changing their coalition during the collaboration among the other actors; (iii) to identify the general ‘policy belief’ that drove the actors to form the coalition; (iv) to determine the main factors that determine the selection of actor for coalition and (v) to assess the influence of the capacity to mobilise resources on the policy objectves during coalition. The researcher mainly refes and adapts to the theory ACF Framework by Sabatier & Jenkins-Smiths (1999) to understand the coalition among the actors in this study. This study applies the methodological triangulation where the researcher aims to check and establish the validity in the studies.